The analgesic effects of intrathecal morphine in comparison with ultrasound‐guided transversus abdominis plane block after caesarean section: a randomised controlled trial at a Ugandan regional referral hospital. (1st November 2018) - Kwikiriza, A.; Kiwanuka, J. K.; Firth, P. G.; Hoeft, M. A.; Modest, V. E.; Ttendo, S. S.
Summary: Both transversus abdominis plane block and intrathecal morphine may produce prolonged postoperative analgesia, but the respective clinical outcomes of these anaesthetic techniques in resource‐limited settings are not well described. We randomly assigned patients undergoing caesarean section to receive a hyperbaric bupivacaine (10 mg) spinal anaesthetic followed by an ultrasound‐guided transversus abdominis plane block, or a hyperbaric bupivacaine (10 mg) spinal anaesthetic with 100 mcg intrathecal morphine, followed by a postoperative sham block. Supplemental postoperative analgesia included self‐administered oral diclofenac 50 mg and paracetamol 1 g every 8 h. Numerical pain rating scores, the need for rescue medication, side‐effects and patient satisfaction were recorded at 8, 16 and 24 h. We enrolled a total of 130 patients, with 65 women in each group. The mean numerical rating score for intrathecal morphine vs. transversus abdominis plane blocks at 8 h were: at rest, 2.5 vs. 3.1 (p = 0.04); with coughing, 4.3 vs. 4.8 (p = 0.07); and with movement, 3.6 vs. 4.2 (p = 0.06). At 16 h, respective scores were: 2.9 vs. 3.1 (p = 0.40) at rest; 4.0 vs. 4.3 (p = 0.19) with coughing; and 4.8 vs. 5.0 (p = 0.33) with movement. At 24 h, the respective scores were: 2.9 vs. 2.3 (p = 0.01); 4.6 vs. 4.2 (p = 0.04) with coughing; and 3.9 vs. 3.4 (p = 0.02) with movement. The need for rescue medication and the incidence of pruritis, sedation and nausea and vomiting were similar in both groups. Patient satisfaction with pain control was similar in both groups, with the majority of patients reporting satisfaction as good or excellent. Intrathecal morphine and transversus abdominis plane block provided clinically similar outcomes for pain relief after caesarean section.